Phonological System and Genetic Classification of Tai in Phulaenchang Village, Phulaenchang Sub-district, Na-khu District, Kalasin Province - Hannok, Siraphat; Trongdee, Thananan (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were to analyze the sound system as well as relationship studying of Thai Pulaenchang language, Sub-district Na-khu District Kalasin Provice, there are Phu Thai and also Lao languages. The educations has been using the interview method of major teller language. By using the word lists approximately 1630 words. And took the obtained information to analyze for searching the consonant units, vowel and tonal units. And to compare the sound changes in the Phu Thai and Lao languages that have already been researched. The research found that the sound system found Thai Pulaenchang language. There are a single consonant sound 19 units. Which could appear as a consonant in all 19 phonemes and 9 phonetic consonants. 1 sound consonant, appears as the first syllableonly. There are 18 single vowel sounds. Mixed vowel 3 sounds as well as tonal 5 sound units. For proving of the descent relationship of Pulaenchang local with Phu Thai languages so Lao language is still used to compare the sound changes in the words of Pulaenchang local with Phu Thai Guchinarailanguage, Phu Thai Nongsung and all 5 Lao languages consists of, Lao Luang Prabang language, Lao Vientiane language, Lao Savannakhet language, Lao Jumpasak language, Lao Attapeurlanguage. It could be concluded that Pulaenchang language did not Phu Thai due to There are differences in the tonal development and vowel change obviously therefore when compared with Lao language all 5languages. It found that Pulacnchang language had changes in sound, which was a shared innovation in sound. Especially the most tonal similar to Lao Savannakhet language.